Therapeutic journeys: the hopeful travails of stem cell tourists - Petersen, A.; Seear, Kathryn; Munsie, M. (John Wiley & Sons, 2014)
The recent growth of so-called stem cell tourism reflects the high optimism that currently surrounds stem cell science. Stem cell treatments for various conditions are increasingly advertised over the Internet as being available at hospitals and clinics around the world. However, most are clinically unproven. Despite numerous warnings from scientists about the dangers posed by such treatments, many individuals are evidently prepared to take the risk, sometimes on more than one occasion. This article explores the dynamics of hope that underpin stem cell tourism. Drawing on ideas from the sociology of hope, as applied to biomedicine, the article explores how hope is constructed and shapes actions in relation to stem cell treatments. Making reference to the findings from an Australian study of patients and carers who travelled overseas to receive stem cell treatments, it is argued that hope has an ambiguous significance in the context of deregulated health care. As we explain, this has implications for patients' and carers' treatment decisions and experiences. The findings are discussed in light of current responses to stem cell tourism.